Endotoxaemia in cystic fibrosis: response to antibiotics. Issue 10 (October 1983) - Taylor, G; Stern, C; Silverman, M; Mearns, M
Abstract : In a study of 6 children with cystic fibrosis receiving intravenous antibiotics for pseudomonas lung infection, serum endotoxin values were monitored by a modification of the limulus lysate technique. The values fell with treatment, reflecting a response that was not always apparent on clinical assessment. Endotoxin concentrations may offer a more precise way of monitoring the effects of antibiotic treatment in CF patients.